Ageing, spirituality, and well-being - Jewell, Albert (Jessica Kingsley Publishers, 2004)
How can we promote the enduring well-being of those who are moving into the 'fourth' age of life? Ageing, Spirituality and Well-being explores how well-being is not about physical health alone; having purpose in life and continual spiritual growth are vital elements for older individuals. This book provides guidance on how the particular spiritual needs of this age group can be defined and addressed, and how meaningful care and support can be given. The contributors use their expertise in the fields of medicine, theology and the social sciences to explore ways of overcoming obstacles and findi.